Patient Interest in Robotic Total Joint Arthroplasty Is Exponential: A 10-Year Google Trends Analysis - Joseph C. Brinkman, MD; Zachary K. Christopher, MD; M. Lane Moore, BS; Jordan R. Pollock, BS; Jack M. Haglin, MD; Joshua S. Bingham, MD (Arthroplasty Today, 2022)
Background: The use of robotics in arthroplasty continues to increase. Patient demand, patient expectations, and patient-directed marketing by industry and care providers each likely contributes to its increasing popularity. Trends in patient interest have not been well described. We used the online Google Trends tool to analyze trends in national public interest toward robotic and nonrobotic arthroplasty between 2011 and 2021. Material and methods: Google Trends online was queried for search terms related to nonrobotic hip and knee arthroplasty in addition to robotic hip, robotic knee, and general robotic arthroplasty between January 1, 2011, and December 31, 2021. Results: Google Trends Data demonstrated a significant linear increase in online searches related to nonrobotic total knee and hip arthroplasty. Online search volume for robotic hip arthroplasty was significant and linear, while that of robotic knee arthroplasty was significant and exponential. When combined, robotic joint arthroplasty demonstrated an exponential trend over the 10-year period. This increase was noted to be statistically significant when compared with nonrobotic arthroplasty search volume. Conclusion: Our study demonstrates that public interest in robotic total joint arthroplasty has increased significantly from 2011 through 2020. When compared with online search volume for conventional arthroplasty, this increasing growth is statistically significant. Public interest in robotic arthroplasty is anticipated to continue to increase, and care providers should be aware of this trend that impacts patient perceptions and expectations. Despite significant growth in interest for robotic arthroplasty, there is incomplete evidence supporting its use over nonrobotic arthroplasty. Additional high-quality studies are needed to inform provider decision-making and appropriately guide public interest in robot-assisted arthroplasty.